Experimental Research Based on the Optical Fiber Sensing Technology for a Jacked PHC Pipe Pile Penetration Process - Songkui Sang; Yonghong Wang; Jiaxiao Ma; Mingyi Zhang (Advances in Civil Engineering)
The aim of this work is to explore the influence of the end resistance and shaft resistance regarding the mechanism for jacked pile penetration and the load-transfer rule during the penetration process. A full-scale field test was conducted in an actual project located in Dongying, Shandong Province, China. In this test, the axial strain experienced by two closed Prestressed High-strength Concrete (PHC) pipe piles during jacking into layered soil was monitored successfully using Fiber Bragg Grating (FBG) sensors mounted on the pile shaft. The experimental results show that FBG sensors have a good stability, strong antijamming performance, and can effectively monitor the pile stress. The variation law of the jacking force reflects the distribution of the soil layer, and the hardness of the soil layer at the pile end limits the pile force. When the pile end enters the silt layer from the clay layer, the jacking force and shaft resistance increase by 2.5 and 1.7, respectively. The shaft resistance accounted for 44.99% of the jacking force. The end resistance is affected by the mechanical properties of soil, and the end resistance of the silt layer is approximately twice that of the clay layer. The end resistance of the silt layer accounted for 59.84% of the jacking force. When the pile end enters the soft soil layer from the hard soil layer, the impact of the pile driving speed and the tangential force on the surface of the pile body must both be considered. During the pile penetration process, as the penetration depth increases, the radial stress on the pile side at a given depth is gradually released, while the shaft resistance at the pile side degrades significantly.